Error Analysis of Consonant Pronunciation in Arabic Language among Fifth-Grade Students - Pamungkas, Muhammad Ibnu; Ahmad Satibi, Dede; Zakhratunnisa, Alwi; Lestari, Aas (UIN Sunan Gunung Djati Bandung, 2024)
Language teaching and error analysis are integral in Arabic language education, particularly evident among fifth-grade students at SD Tunas Harapan Ar-Raudhah, who face challenges in mastering Arabic pronunciation. These errors occur due to differences between the Indonesian and Arabic sound systems, which cause difficulties. This study included a total of 9 students as its sample group and focuses on analyzing pronunciation errors made by fifth-grade students of SD Tunas Harapan Ar-Raudhah to find out what letters often have errors in pronunciation and find out the factors that cause these errors, as well as finding and providing specific treatments to overcome and reduce the percentage of student errors. The method used in this research is descriptive qualitative with simak catat technique. The results showed 116 errors in Arabic consonant pronunciation (75.8%) during the pre-test, with the highest errors in three letters: dza, qaf, and 'ain. During the post-test, there were 37 errors (24.2%); this shows that the percentage of student errors decreased. The findings underscore the importance of tailored interventions in addressing pronunciation difficulties and contribute to refining language teaching strategies. Future research should explore alternative methodologies and replicate the study with larger student cohorts to enhance generalizability across diverse educational settings, further advancing effective Arabic language instruction